Kenya Economic Update, April 2019, No. 19 : Unbundling the Slack in Private Sector Investment – Transforming Agriculture Sector Productivity and Linkages to Poverty Reduction - World Bank Group (World Bank, Nairobi, 2019)
The Kenyan economy rebounded in 2018 and economic activity in the first quarter of 2019 was healthy, although emerging drought conditions could curtail GDP growth for the remainder of the year. The economy expanded by 6.0 percent in the first three quarters of 2018 compared to 4.7 percent during the same period in 2017 driven by strong private consumption in part due to improved income from agricultural harvests in 2018, remittance inflows, and lower food prices. The Bank's GDP growth estimate for 2018 is about 5.8 percent. A strong pick-up in economic activity in Q1 of 2019 was reflected by real growth in consumer spending and stronger investor sentiment. Nonetheless, a delayed start to the March-May 2019 "long" rainy season could affect the planting season-resulting in poor harvests. In addition, ongoing emergency intervention to address food shortages in several counties could impose fiscal pressure constraining capital spending. These developments have slowed the growth forecast for 2019 and for the medium term relative to our October 2018 Update. Inflation remains within the government's target range of 5±2.5 percent. Headline inflation averaged 4.7 percent in 2018 compared to 8.0 percent in 2017, primarily due to the slowdown in food inflation, which in turn offset a temporary acceleration in energy prices. Further, core inflation has remained below 5 percent, suggesting benign underlying demand pressures. With low inflation, monetary policy could be more accommodative to support growth if needed, but with interest rate caps tied to the policy rate, further loosening would be constrained. The low inflationary pressure has also been supported by a stable local currency. The shilling has traded within a narrow band of Ksh100/US Dollas-Ksh.103/US Dollars in 2018, thereby serving as a nominal anchor to inflationary expectations